Methods of formation of simple personal names in Tuvan - Suvandii, Nadezhda D. (The New Research of Tuva, 2020)
The article presents an overview of the most widespread methods of forming simple personal names, or anthroponyms, in Tuvan language. The sources for the study were over 500 personal names collected by the author in 2019 in the course of linguistic expedition to Mongolian Tuvans (sum Tsengel, Bayan Ölgii aimag, and sum Buyant, Khovd aimag), as well as in several rayons of Tuva: Mongun-Taigin, Ovyur, Bay-Tangin, Barun-Khemchik and Dzun-Khemchik. The author also used entries on personal names from the archives of her expeditions for the previous twenty years. Personal names have been found to fall into two groups: simple productive and simple non-productive. The latter were formed by the lexico-semantical method from common nouns belonging to a variety of semantic groups. The former much larger, group was formed morphologically, by adding to the stem one of the plethora of affixes in accordance to a particular model, 15 of which have been identified.